Propriedades fotocrômicas e eletrocrômicas dos filmes de WO3, WO3:Li+ e WO3:Li+:ZrO2 - Landarin, Daiane Mendes (2014)
The energy issue is one of the points of greatest relevance. Studies show the implications and influences both environmentally, and socially and economically. And the main alternative to overcome this energy crisis are the possible alternative sources of energy as well as the creation of new technologies that will reduce energy consumption. Chromogenic materials are being widely studied and is this project is inserted with the purpose to study, prepare and characterize thin films with electrochromic properties. Specifically thin films of tungsten oxide doped and non-doped, which will be part of the working electrode of an electrochromic device, with the objective of obtaining satisfactory photo and electrochromic properties, such as reversibility, optical memory, stability and durability. The preparation of the oxides was performed by the Sol-gel process, where the sols were obtained from tungsten metal precursors having as the lithium salt (LiCF3SO3) and zirconium alkoxide (zirconium isopropoxide) as precursors, ethanol as solvent and glacial acetic acid as catalyst. The films were prepared by dip-coating technique on a substrate (FTO Pilkington Glass). A systematic study was conducted to obtain films with photochromic and electrochromic properties desired. The deposited films after rapid hydrolysis in the air were submited to heat treatment at 240 ° C for one hour in air atmosphere. The electrochromic thin films of WO3 and WO3 doped were studied by electrochemical techniques (cyclic voltammetry, chronocoulometry and impedance), structural (X-rays), morphological (AFM) and also optical (transmittance). Have the photochromic films of WO3 doped and undoped were studied from optical measurements (UV-Vis) in order to study the coloration process.